Odpowiedzi

2010-02-13T16:07:37+01:00
-2x+5y
-1/6m+7/24n-1/12
0,01xkwadrat - 0,02x
-2x kwadrat-0,25x+5,5
2010-02-13T16:08:20+01:00
3x-2y-5x+7y=-2x+5y

1/3m+1/4n-1/2m+1/24n-1/12 |*24
8m+6n-12m+n-2=-4m+7n-2

0,05x-0,07x²-0,07x²+1,2x²-0,07x-1,05x²=0,01x²-0,02x

6x²+0,5-0,25x-8x²+5=-2x²-0,25x+5,5


2010-02-13T16:08:21+01:00
3x-2y-5x+7y = -2x + 5y

1/3m+1/4n-1/2m+1/24n-1/12 = 2/6m + 6/24n - 3/6m +1/24n - 1/12 = -1/6m + 7/24 n - 1/12

0,05x-0,07x kwadratowych-0,07x kwadratowych+1,2x kwadratowych-0,07x-1,05x kwadratowych = 1,18 x -1,29x²

6x kwadratowych+0,5-0,25x-8x kwadratowych+5 = -2x² - 0,2 x + 5